Spatio-Temporal Analysis of Tuberculosis Clusters in a Region of Topographic Diversity: A Case Study from West Sulawesi Province, Indonesia - Fahrul Islam; Haeranah Ahmad; Fajar Akbar; Ain Khaer; Iwan Suryadi; Muhammad Syukri; Kadar Ramadhan (Journal of Public Health and Pharmacy, 2025)
Introduction: Several studies on tuberculosis (TB) using spatial and time clustering analyses have been conducted in Indonesia, however none have specifically focused on regions characterized by diverse topography. This study aimed to identify geospatial clusters of TB cases in West Sulawesi Province, Indonesia, an area known for its topographic variability.